Perancangan Sistem Kendali Inkubator Bayi Berdasarkan Kestabilan Suhu dan Kelembaban Berbasis Internet Of Things - Dimas Pradika; Elsa Kurnianti; Fermadana; Nur Fahdilah; Nirwan Sinuhaji; Dewi Yohana Br Ginting Ginting; Jenni Veronika Br Ginting (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2023)
A baby incubator is a special device shaped like a glass tube filled with a small mattress for babies. In general, incubators can only be controlled directly, as technology develops, incubators can be controlled without direct touch via the internet of things. This baby incubator control system only uses 1 sensor which functions to detect temperature and humidity instability. As well as using the Arduino Uno R3 microcontroller which functions to control an input output from a system designed to process input data from sensors. The test results show that the system is able to provide information through the android application if it detects an instability of temperature and humidity in the incubator room.